Penerapan Konseling KB Menggunakan Strategi Konseling Berimbang KB Pasca Persalinan pada Bidan di Wilayah Bandung - Lina Haryani; Nanik Cahyati; Mega Dewi Lestari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The Maternity Guarantee Program (Jampersal) where one of its activities is Postpartum Family Planning services with an emphasis on strategies so that all mothers in childbirth can be assisted by health workers and immediately get Postpartum Family Planning Services. However, this opportunity for postpartum family planning services can be missed if the available health workers do not have sufficient capacity and skills to conduct counseling and provide postpartum family planning services. The counseling method in Postpartum Family Planning Services that is currently being developed is the Balanced Counseling Strategy (Strategi Konseling Berimbang) method which focuses more on patients with a shorter and more effective time so as to enable health workers to provide higher quality counseling. At present the SKB method has not yet been implemented for all patients because there is still a shortage of health workers who have not been exposed to the SKB method. With the existence of community service activities carried out by bachelor of midwifery study programs and the Midwife Profession using training methods for all implementing midwives in the Cimahi and West Bandung regions and it is hoped that this can be done for patients, especially postpartum patients.